Altered vascular stiffness and central pulse wave parameters in climacteric women - I. A. Salov; S. N. Tolstov; A. P. Rebrov (IRBIS LLC, 2020)
Aim: to assess changes in parameters of vascular stiffness, central aortic pressure (CAP) as well as reflected pulse wave in women in different phases of the climacteric period.Materials and Methods. An open non-randomized single-center comparative study was conducted with 384 menopausal women subdivided into: Group 1 - 168 women at menopausal transition, Group 2 - 216 women at early postmenopause. A 24-hour blood pressure (BP) monitoring was performed with assessing daily dynamics of parameters of arterial stiffness, CAP and reflected pulse wave. The aortic pulse wave velocity and local aortic stiffness were estimated.Results. It was found that women in early postmenopausal period vs. menopausal transition showed significantly higher values of daily central BP combined with more prominent changes in vascular stiffness. Menopausal women were characterized by lowered difference between nocturnal central and peripheral BP level (less amplified nocturnal vs. diurnal peripheral BP magnitude), which is associated with a greater augmented CAP at this time point. Such pattern was more pronounced in women at postmenopausal period.Conclusion. Women in climacteric period were found to have increased vascular stiffness combined with elevated CAP, decreased amplification of pulse pressure and increased amplitude of the reflected pulse wave may be associated with increased risk of cardiovascular complications. Much more prominent changes were noted in women in early postmenopausal period.